Professor Jozef Zwislocki (1922 – 2018) - Edward OZIMEK (Archives of Acoustics)
Biography of Jozef John Zwislocki (March 22, 1922 – May 14, 2018) – Polish-born American neuroscientist. Granted fellowship into the Acoustical Society of America, as well as membership to the United States National Academy of Sciences, Polish Academy of Sciences, American Association for the Advancement of Science, and Association for Research in Otolaryngology (among others). He worked at Federal Institute of Technology in Zurich, Switzerland, taught at the University of Basel, was on a research fellowship at Harvard University, and was member of the Syracuse University faculty. Owner of twelve patents.